Electrodeposition of Tungsten from Molten KF–KCl–WO3 and CsF–CsCl–WO3. (8th September 2020) - Nohira, Toshiyuki; Meng, Xianduo; Ide, Tatsuya; Norikawa, Yutaro; Yasuda, Kouji
Abstract : The electrodeposition of W films was investigated in KF–KCl eutectic melts after adding 0.5–2.0 mol% of WO3 at 923 K. Cyclic voltammetry at a Ag electrode suggested that the electrodeposition of W from W(VI) ions proceeds from 1.65 V vs. K + /K. Electrodeposition of α-W was confirmed by XRD analysis. The effect of current density and added amount of WO3 on the morphology of W films was investigated by surface and cross-sectional SEM, which indicated that the best W film having thickness of ca. 15 μm was obtained at 12.5 mA cm −2 and 2.0 mol% of WO3 . Although the film thickness was increased to ca. 30 μm by increasing the charge density, the surface roughness was significantly increased. To suppress the growth of crystal grains, electrodeposition of W was also investigated in CsF–CsCl eutectic melts at lower temperature of 873 K. The XRD confirmed the existences of both α-W and β-W in the W films. The SEM observations revealed that dense and smooth W films having thickness of ca. 30 μm was successfully obtained.